Space Vector Pulse Width Modulation Scheme for a Seven-Phase Voltage Source Inverter - Mohd. Arif Khan; Atif Iqbal; Sk Moin Ahmad (Institute of Advanced Engineering and Science, 2011)
This paper analyses a simple space vector PWM (SVPWM) scheme for a seven-phase voltage source inverter. At first the conventional method of producing sinusoidal output voltage by utilizing six active and a zero space vectors are used to synthesis the input reference and then new PWM scheme called time equivalent space vector PWM is presented. A comparison of the proposed scheme with the conventional scheme is presented based on various performance indices. Extensive Simulation results are provided to validate the findingsDOI: http://dx.doi.org/10.11591/ijpeds.v1i1.72